Allergic diseases among children with autism spectrum disorders - Akpınar, Fatma; Kutluk, Günsel; Özomay, Gülcan; Yorbık, Özgür; Çetinkaya, Feyzullah (Wiley-Blackwell, 2015)
Background: Allergic diseases (e.g. asthma, allergic rhinitis and atopic dermatitis) are very common among children and are still increasing worldwide. On the other hand autism spectrum disorder (ASD) is also on the rise.
Keywords: Allergic; Autism; Spectrum